Effects of simulated N deposition on photosynthesis and productivity of key plants from different functional groups of alpine meadow on Qinghai-Tibetan plateau. (August 2019) - Shen, Hao; Dong, Shikui; Li, Shuai; Xiao, Jiannan; Han, Yuhui; Yang, Mingyue; Zhang, Jing; Gao, Xiaoxia; Xu, Yudan; Li, Yu; Zhi, Yangliu; Liu, Shiliang; et al.
Abstract: Nitrogen (N) deposition may alter physiological process of plants in grassland ecosystem. However, little is known about the response mechanism of individual plants in alpine regions to N deposition. We conducted a field experiment, and three treatments including 0 kg Nha -1 year −1 (CK), 8 kgNha -1 year −1 (Low N), and 72 kg N ha -1 year −1 (High N) were established to simulate N deposition in alpine meadow of Qinghai-Tibetan plateau. Our objectives were to determine the influence of N deposition on photosynthesis of different functional types of herbage species in alpine meadow, and finally characterize the links of plant productivity and photosynthesis with soil nutrients. The results showed that responses of alpine plants were species-specific under N deposition. Compared with grass species Agropyron cristatum and forb species Thalictrum aquilegifolium, the sedge species Carex melanantha was much more sensitive to N deposition; a lower N load (8 kgNha -1 year −1 ) can cause a negative effect on its photosynthesis and productivity. Additionally, N deposition can promote plant N uptake and significantly decreased the C (carbon)/N (nitrogen) ratio. Compared with CK and low N deposition, high N deposition inhibited the photosynthesis and growth of the forb species Thalictrum aquilegifolium and sedge species Carex melanantha . In all three functional types of herbage species, the grass species A. cristatum tended to show a much higher photosynthetic capacity and better growth potential; thus, suggesting that grass species A. cristatum will be a more adaptative alpine plants under N deposition. Our findings suggested that plant photosynthetic responses to N deposition were species-specific, low N deposition was not beneficial for all the herbage species, and N deposition may change plant composition by the differential photosynthetic responses among species in alpine grassland. Plant composition shift to grass-dorminant in alpine regions might be attributed to a much higher photosynthetic potential and N use efficiency of grass species. Graphical abstract: Image 1035 Highlights: The photosynthesis of alpine plants species-specifically response to N deposition. The responses of the alpine plants to nitrogen deposition was closely related to soil N. Sedge species may sensitively response to N deposition. Grass species might have a much higher photosynthetic capacity and better growth potential.